Activated charcoal and reduced graphene sheets composite structure for highly electro-catalytically active counter electrode material and water treatment. (6th March 2020) - Riaz, Rabia; Ali, Mumtaz; Maiyalagan, T.; Arbab, Alvira Ayoub; Anjum, Aima Sameen; Lee, Seoyun; Ko, Min Jae; Jeong, Sung Hoon
Abstract: In quest of finding a sustainable solution for metal-free counter electrode materials, reduced graphene oxide (rGO) is emerged as the best alternative due to its intrinsic high electrocatalytic activity. However, owing to its two-dimensional sheets like structure, there is re-stacking of rGO sheets, which reduces exposed surface area and hinders in electrolyte diffusion. To avoid these issues, activated charcoal (AC) is explored as an active spacer material between rGO sheets, for the first time. By loading an optimum concentration of AC in rGO, a high porosity, high conductivity, and high concentration of active sites were gathered in the single composite structure. Such synchronized features of the proposed composite were utilized for Pt-free counter electrode application in dye-sensitized solar cell (DSSc). The composite structure showed high electrocatalytic activity, with a low charge transfer resistance of 0.7 Ω, which is far lower than Pt and rGO (8.5 Ω and 7.5 Ω). The DSSc fabricated with optimized composite showed power conversion efficiency of 8.6%, compared to Pt-based DSSc with 7.9% efficiency. Additionally, the potential of the electrode was also tested for the electro-photocatalytic (99%) degradation of methylene blue dye from water, in 60 min. The proposed highly efficient nanocomposite structure possesses the highest efficiency as compared to other previously studied rGO based counter-electrodes. Graphical abstract: Image 1 Highlights: Activated charcoal is explored as an active spacer material for rGO sheets. Composite structure showed a power conversion efficiency of 8.6%. Low charge transfer resistance of 0.45 Ω was observed, in the porous structure. The proposed electrode electro-photocatalytically degraded 99% methylene blue dye.